2016
DOI: 10.1016/j.esxm.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Sexual Medicine Specialists Toward Premature Ejaculation Diagnosis and Therapy

Abstract: IntroductionPremature ejaculation (PE) is one of the commonest sexual dysfunctions in men. Because the definition of and guidelines for the management of PE have been revised in recent years, our understanding of PE has changed.AimTo investigate the clinical practice patterns of sexual medicine specialists regarding the diagnosis and treatment of PE.MethodsAttendees of the 17th Annual Congress of the European Society of Sexual Medicine, held in February 2015 in Copenhagen, Denmark, were asked to participate in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Therefore, we likely captured a representative sample of the conference delegates. The sample size corresponds to that of previous similar studies 17 . Further limitations include the small absolute number of LI-ESWT users and the fact that most have their practice in a private setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we likely captured a representative sample of the conference delegates. The sample size corresponds to that of previous similar studies 17 . Further limitations include the small absolute number of LI-ESWT users and the fact that most have their practice in a private setting.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size corresponds to that of previous similar studies. 17 Further limitations include the small absolute number of LI-ESWT users and the fact that most have their practice in a private setting. In this regard, we lack data on LI-ESWT regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Similar social psychology, historical, and cultural effects are more evident in Asia, which may explain why the self-reported rate of ejaculatory abnormality is only 2% in these regions, while in Europe and the United States, it can reach 81.9% (14,16). Furthermore, Shechter et al pointed out that factors such as clinical practice, educational background, and the own sexual experiences of the physicians may constitute reasons for an underlying biased diagnosis of PE (17). These findings suggest that the misconceptions regarding the subjective ejaculatory symptoms and clinical history may lead to a biased patient history regarding PE and erroneous diagnosis in clinical practice.…”
Section: History Inquirymentioning
confidence: 99%
“…[8, 9] However, few men with PE had sought treatment from a physician or therapist. [10] The results from Carson et al showed that only 1% of men aged ≥ 40 reported that they had received treatment for PE. [11] Numerous factors are obstacles to PE treatment, some of which are related to the patient's inner resistance.…”
Section: Introductionmentioning
confidence: 99%